MECHANISMS OF CRYSTALLIZATION PROCESS OF METALS AND ALLOYS - V. Yu. Stetsenko (Литьë и металлургия, 2013)
New mechanisms of the metals and alloys crystallization processes on the basis of the thermodynamic analysis of the homogeneous and heterogeneous nucleation processes are given.